Essentials of working capital management - Sagner, James S. (Wiley, 2011)
A comprehensive primer for executives and managers on working capital management. With limited access to credit and short term funding, it is increasingly important that companies focus on working capital management to free up funds and optimize liquidity. Written in the easy-to-follow Essentials Series style, Essentials of Working Capital Management covers the main components of working capital: the latest trends around working capital; a range of working capital topics, including cash management, banking relations, accounts receivable, inventory, accounts payable, and foreign exchange; the efficient utilization of current assets and liabilities of a business through each phase of the operating cycle; and the gathering and management of information and forecast data to effectively use funds and identify risk. Focused on how businesses can continue to be successful in these difficult times, specifically in relation to the limited credit available to businesses, this book puts practical guidance at your fingertips so you can put them to work right away. A comprehensive case introduces each major section of the book, and suggested solutions are included in a book appendix
Keywords: BUSINESS & ECONOMICS / Investments & Securities / General; Wirtschaft; Working capital; Corporations / Finance